2002
DOI: 10.4314/jfta.v7i3.19238
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of processing and microbial changes during fermentation of borde, a traditional Ethiopian beverage

Abstract: Samples of borde from open markets at five localities in southern Ethiopia showed average aerobic mesophilic count (AMC), lactic acid bacteria (LAB) and yeast counts of 9.9, 10.1, and 8.1 log CFU g -1 respectively. Enterobacteriaceae (EB) were <1 to 3.5 log CFU g -1 . The pH was 3.92±0.14. During the traditional production of borde with its four phases, the proportions of ingredients and cooking temperature were measured. Development of pH, titratable acidity, microbial load and mash temperature were monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 19 publications
1
31
1
Order By: Relevance
“…The variation observed between the samples in their pH value could be due to the differences in fermentation time and type of cereals utilized. Based on the finding of this study, cheka had low mean pH value of 3.75, which is lower than that of other Ethiopian traditional beverages such as tella (Yohannes et al., 2013), tej (Gizaw, 2006; Yohannes et al., 2013), borde (Abegaz et al., 2002b), shamita (Ashenafi & Mehari, 1995), kerebo (Rashid, 2013a), and arake (Yohannes et al., 2013). On the other hand, ready to consume cheka had titratable acidity comparable to borde (Abegaz et al., 2002b) but lower titratable acidity than kerebo (Rashid, 2013a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variation observed between the samples in their pH value could be due to the differences in fermentation time and type of cereals utilized. Based on the finding of this study, cheka had low mean pH value of 3.75, which is lower than that of other Ethiopian traditional beverages such as tella (Yohannes et al., 2013), tej (Gizaw, 2006; Yohannes et al., 2013), borde (Abegaz et al., 2002b), shamita (Ashenafi & Mehari, 1995), kerebo (Rashid, 2013a), and arake (Yohannes et al., 2013). On the other hand, ready to consume cheka had titratable acidity comparable to borde (Abegaz et al., 2002b) but lower titratable acidity than kerebo (Rashid, 2013a).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the finding of this study, cheka had low mean pH value of 3.75, which is lower than that of other Ethiopian traditional beverages such as tella (Yohannes et al., 2013), tej (Gizaw, 2006; Yohannes et al., 2013), borde (Abegaz et al., 2002b), shamita (Ashenafi & Mehari, 1995), kerebo (Rashid, 2013a), and arake (Yohannes et al., 2013). On the other hand, ready to consume cheka had titratable acidity comparable to borde (Abegaz et al., 2002b) but lower titratable acidity than kerebo (Rashid, 2013a). Since the pH of the samples were measured once immediately after they had been brought to the laboratory, the investigators believe that the pH of cheka can even be lower than the reported values in this study if determined over a period of time until it turns not safe to consume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beverages have been produced on fairly small scale and usually for local consumption. Among Ethiopian indigenous fermented beverages ÔTella' (Sahle & Gashe, 1991), ÔTej' (Bahiru, Mehari, & Ashenafi, 2001), ÔBorde' (Abegaz, Beyene, Langsrud, & Narvhus, 2002a, 2002bAshenafi & Mehari, 1995;Bacha, Mehari, & Ashenafi, 1998) and ÔShamita' (Ashenafi & Mehari, 1995;Bacha, Mehari, & Ashenafi, 1999) are the most common.…”
Section: Introductionmentioning
confidence: 98%
“…The sharp decrease of EB counts while the other microbial counts (except AAB) increased is due to decrease in pH resulted from the active growth of acid producing microorganisms. The low pH could be responsible for inhibition and inactivation of the growth of EB [23,33,34] Figures 2A and 2B. Phase II: At the beginning of this phase, to the fermenting green and foamy tinisis, powdered malt, powdered leaves of Rhamnus prinoides, pieces of kitta (unleavened bread) and water were separately added to each fermenter and thoroughly mixed. The counts of EB become below detectable level and AAB detection began in traditional fermenter and still not detected in modified fermenter.…”
Section: Changes In Microbial Physical and Chemical Parametersmentioning
confidence: 99%